Caracterização da avaliação farmacêutica da prescrição médica em um hospital universitário - Hodali, Namir Ferreira El (2016)
The hospital pharmacy must control and dispense medicines in a timely manner to optimize the recovery of patients. The implementation of systems and procedures for the control and improvement of health services are increasingly necessary. Objective: To characterize the pharmaceutical assessment of medical prescription of a university hospital in southern Brazil, classifying patients regarding the risk of developing drug related problems, describing pharmaceutical interventions in high-risk patients and the impact of these interventions. Methodology: Cross-sectional study in a university hospital in southern Brazil. The pharmaceutical assessment of prescriptions was performed by the application of a pharmaceutical score. After classification of risk, pharmacists performed pharmacotherapeutic analysis through Micromedex and Uptodate databases. Pharmaceutical interventions were included in the records of the patients and after, it was verified how many and which recommendations had been used. Results: 282 prescriptions for patients treated by 15 different medical specialties were assessed, being 150 (53%) classified as high risk to develop pharmacotherapeutic problems. 265 pharmaceutical interventions in high-risk patients were performed. Of these, the main ones were: potential interactions and dose adjustment. The health team was favorable concerning 37 (14%) of the interventions. Conclusion: The prescriptions assessed by the pharmacists presented different risks for the patient to develop pharmacotherapeutic problems. With the use of a pharmaceutical score it was possible to prioritize situations of high risk for developing pharmacotherapeutic problems and make recommendations to health staff. The incorporation of clinical pharmacy services is needed for patients, health professionals and institutions.